Metachronous mucinous breast carcinoma and mucinous pancreatic cystadenoma in a patient with metabolic comorbidities; case report and a literature review - Teodora Gabriela Alexescu; Irina Obada; Angela Cozma; Mirela Georgiana Perne; Olga Hilda Orășan; Vasile Negrean; Iacob Domșa; Victoria Ruta; Simina Felicia Țărmure (Journal of Mind and Medical Sciences)
Mucinous breast carcinoma is a rare subtype of mammary neoplasm encountered in medical practice. It represents approximately 1-6% of all breast cancers and is more common in postmenopausal women. There are two subtypes of mucinous breast carcinoma: pure and mixed. We report the case of a 73-year-old Caucasian woman diagnosed with mucinous pancreatic cystadenoma in 2007. She underwent a surgical procedure involving pancreatectomy of the body and tail, along with multiple known cardiovascular and metabolic comorbidities. In November 2019, during a clinical-biological evaluation for associated diseases, a mucinous carcinoma of the right breast was accidentally detected and later confirmed through further investigations. For treatment, a surgical procedure was performed involving lower right quadrantectomy with right axillary lymph node dissection. The postoperative clinical course was favorable. In conclusion, we present the case of a patient diagnosed with mixed mucinous breast carcinoma, without axillary lymph node invasion. Postmenopausal women with diabetes, overweight, and obesity have an increased susceptibility to breast cancer, with our patient having all these risk factors. To date, no study has demonstrated the genetic or radiation implication in the occurrence of mucinous carcinomas, nor the possible development of mucinous carcinomas in series in the same patient. Yet, current data are insufficient to provide recommendations for the screening of malignant mucinous tumors in subjects with significant cardiometabolic risk factors.